A short-term ingestion of fructo-oligosaccharides increases immunoglobulin A and mucin concentrations in the rat cecum, but the effects are attenuated with the prolonged ingestion. Issue 9 (2nd September 2014) - Komura, Mika; Fukuta, Tomonori; Genda, Tomomi; Hino, Shingo; Aoe, Seiichiro; Kawagishi, Hirokazu; Morita, Tatsuya
Abstract: We examined the effects of fructo-oligosaccharides (FOS) on IgA and mucin secretion in the rat cecum after different ingestion periods. Rats were fed a control diet or a diet containing FOS for 1, 2, 4, and 8 wk. FOS ingestion greatly increased IgA and mucin concentrations at 1 and 2 wk, but the effects were disappeared or attenuated at 4 and 8 wk. After 1 wk, FOS induced higher lactobacilli and lactate concentrations and lower cecal pH in the cecum, but the alterations were moderated with the prolonged ingestion accompanying with increasing short-chain fatty acid concentrations. At 1 and 2 wk, FOS increased IgA plasma cells and polymeric immunoglobulin receptor expression in the cecal mucosa and strongly depressed fecal mucinase activities related to the lower cecal pH. These findings may explain the FOS-induced early elevation of IgA and mucin. Clearly, FOS effects on IgA and mucin secretion considerably differ depending on the ingestion period. Graphical abstract: : A short-term ingestion of FOS greatly increased the cecal concentrations of IgA and mucin in rats, but these effects were disappeared or attenuated with the prolonged ingestion.